Sensitisation to molecular components in patients with atopic dermatitis, relation to asthma bronchiale and allergic rhinitis. Issue 1 (1st January 2020) - Čelakovská, J.; Bukač, J.; Vaňková, R.; Krcmova, I.; Krejsek, J.; Andrýs, C.
ABSTRACT: Backround and aim: To evaluate the sensitisation to molecular components in atopic dermatitis patients with the use of Multiplex ISAC testing. Method: The complete dermatological and allergological examination including the examination of the sensitisation to molecular components with Multiplex ISAC testing was performed. Results and conclusion: Eighty one patients were examined – 40 men, 41 women, average age 41.7 years. The positivity was recorded most frequently to molecular components of timothy, birch, house dust mite, animals dander, bermuda grass, peach, apple, hazel pollen, kiwi, peanut and hazelnut, Alternaria and Aspergillus. Molecular components such as Equ c 1 (Horse), Alt a 6 (Alternaria), Fel d 1, Fel d 4 (Cat) and Can f 1, Can f 5 (Dog) are recorded with the significant higher occurrence simultaneously in patients suffering from severe form of AD, asthma bronchiale and allergic rhinitis; these molecular components play the most important role in the atopic march.